1999
DOI: 10.1029/1998jd100055
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft lidar observations of an enhanced type Ia polar stratospheric clouds during APE‐POLECAT

Abstract: and optical modeling, we investigate the possible evolution of this cloud assuming either in situ freezing of ternary HNOa/H2SO4/H20 droplets as nitric acid trihydrate, or the formation of the clouds in mountain waves over the east coast of Greenland, as suggested by a mountain wave model. Best agreement with the observations was obtained by assuming mountain-wave-induced cloud formation, which yields nitric acid trihydrate particles with much higher total mass than achieved by assuming synoptic-scale freezing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
77
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 25 publications
6
77
0
Order By: Relevance
“…They concluded that during the "PSC season" when the background temperature was close enough to the NAT formation temperature (T NAT ), derived in Hanson and Mauersberger (1988), gravity wave perturbations influence PSC formation approximately 15% of the time. Interestingly, this value is similar to the findings of Felton et al (2007) who concluded Type Ia enhanced PSCs, which are likely to be NAT crystals with unusually large lidar backscattering ratios which appear down wind of mountain wave-induced ice clouds (Tsias et al, 1999), make up 11% of the clouds observed during the SAGE III Ozone Loss and Validation Experiment (SOLVE) campaign in winter 2000 in the Northern Hemisphere. However, the warmer mean temperature in the Arctic means that this is likely to be coincidental.…”
Section: Introductionsupporting
confidence: 76%
“…They concluded that during the "PSC season" when the background temperature was close enough to the NAT formation temperature (T NAT ), derived in Hanson and Mauersberger (1988), gravity wave perturbations influence PSC formation approximately 15% of the time. Interestingly, this value is similar to the findings of Felton et al (2007) who concluded Type Ia enhanced PSCs, which are likely to be NAT crystals with unusually large lidar backscattering ratios which appear down wind of mountain wave-induced ice clouds (Tsias et al, 1999), make up 11% of the clouds observed during the SAGE III Ozone Loss and Validation Experiment (SOLVE) campaign in winter 2000 in the Northern Hemisphere. However, the warmer mean temperature in the Arctic means that this is likely to be coincidental.…”
Section: Introductionsupporting
confidence: 76%
“…While this cannot establish a freezing process above (T ice ), since the ice phase may be very short lived compared to a long lived hydrate phase initiated by the ice, it is consistent with a freezing process above T ice which would help explain many observations of solid PSC particles (Drdla et al, 2002a). High number concentrations of small solid particles in equilibrium with the gas phase could be nucleated in mountain wave conditions (Tsias et al, 1999). Other investigations show PSCs to be dominated by liquid particles with only small concentrations of solid particles growing to large sizes; an observation which calls for a selective nucleation mechanism (Drdla et al, 2002b).…”
Section: Introductionmentioning
confidence: 65%
“…Under quasi-stationary meteorological conditions these mesoscale clouds do not strongly vary their spatial position relative to the ground, and in the air flowing through them particles nucleate, grow, and evaporate continuously over a period of hours. Previously, particle evolution in wave PSCs was successfully studied based on quasi-Lagrangian observations acquired with airborne lidars (Carslaw et al, 1998;Tsias et al, 1999;Wirth et al, 1999;Dörnbrack et al, 2002;Hu et al, 2002;Fueglistaler et al, 2003). A similar study that rests upon data obtained with ground-based lidars has not been published so far, probably mainly due to the fact that they lack the additional dimension that is offered by aircraft observations.…”
Section: Introductionmentioning
confidence: 99%
“…Gobbi et al, 1998;Stein et al, 1999;Toon et al, 2000;Biele et al, 2001). In this case, the interpretation of the PSC data in terms of the two coexisting particle classes can be improved if backscatter coefficients (or backscatter ratios) are studied separately for both states of polarization, since droplet scattering adds to the parallel-polarized lidar signal alone (single scattering assumed) whereas the light backscattered from nonspherical solid particles has both parallel-and perpendicular-polarized components.…”
Section: Polarization-sensitive Backscatter Ratiosmentioning
confidence: 99%